COMPARISON OF CHARACTERISTICS OF PHOTONS FLUXES VARIOUS ENERGIES IN THE DEVELOPMENT OF SOLAR GAMMA FLARES - Minasyants, G.S.; Minasyants, T.M.; Tomozov, V.M. (Academic Scientific Journal of Computer Science, 2020)
The characteristics of photons fluxes of various energies during the development of flares with highenergy gamma rays are considered. Observations on FERMI, SDO, GOES spacecraft were used. Photons fluxes with energies Ek = (12-25) keV, Ek = (50-100) keV and Ek > 100 MeV for 19 flares events were compared. Comparison of quantitative and temporal characteristics of photons profiles of X-ray energy range with properties of bright flares plasma showed that for almost all events the moments of onset of peaks (12-25) keV and maximum values (50-100) keV of photons in counts/s refer to the time interval from the beginning of flares development within 22 minutes. The same result is noted for events with the most intense maximum fluxes in (γ·cm-2· s-1) for high energy photons > 100 MeV. This supports the assumption of the most effective acceleration of particles during the simultaneous development of the direct flare process and the accompanying coronal mass injection, resulting in the creation of maximum fluxes values of highly energetic gamma photons. Flares events with the most intense maximum fluxes in (γ·cm-2· s-1) for high energy photons > 100 MeV do not show the highest values of the number of photons in the X-ray energy ranges, indicating differences in the efficiency of photons formation mechanisms of different energies. According to observations, the most likely source of quantitative amplification of flares photons with energies (12-25) keV is the results of bremsstrahlung radiation of bright flares emission in corona, and for photons with energies (50-100) keV - in the area of upper photosphere and temperature minimum.